Reform of Clinical Research Regulations - Strauss, David H; Hurley, Elisa A; Capron, Alexander M; Emanuel, Ezekiel (The New England journal of medicine, 2016)
To the Editor: In his Perspective article, Emanuel (Dec. 10 issue) 1 argues that the Notice of Proposed Rulemaking (NPRM) issued by 16 federal agencies in September to revise the Common Rule that governs research with human beings conducted at institutions receiving federal funding 2 may be imperfect but represents the best chance for needed reform. Sound policymaking does not, however, rely on risky experimentation of the sort the NPRM represents. The NPRM is a troublingly incomplete product: internally inconsistent, dependent on untested assumptions, and too inchoate to be ready for promulgation with just some minor editing. The document, which had largely . . .